2021
DOI: 10.1017/gmh.2021.21
|View full text |Cite
|
Sign up to set email alerts
|

Contextual factors associated with depression among Northern and Indigenous adolescents in the Northwest Territories, Canada

Abstract: Background Persons in Arctic regions disproportionately experience depression. Knowledge gaps remain regarding factors associated with depression among adolescents in the Northwest Territories (NWT), Canada, where child and adolescent mental health hospitalizations are nearly 2.5 times the national rate. This study assesses correlates of depression among adolescents in the NWT. Methods We conducted a cross-sectional survey with adolescents aged 13–18 in 17 NWT communities. We assessed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…(70,74,81,85,87,88) Contamination was also perceived to affect animal health and the taste and texture of harvested food. (74,87) Mental health: Seventeen articles focused on mental health, and four major factors of mental health were identi ed: alcohol and substance use ( 4),(89-93) family and support networks ( 5),(94-98) gender ( 7), (91,97,(99)(100)(101)(102)(103) and seasonality (3). (97,104,105).…”
Section: Bmi: Body Massmentioning
confidence: 99%
See 1 more Smart Citation
“…(70,74,81,85,87,88) Contamination was also perceived to affect animal health and the taste and texture of harvested food. (74,87) Mental health: Seventeen articles focused on mental health, and four major factors of mental health were identi ed: alcohol and substance use ( 4),(89-93) family and support networks ( 5),(94-98) gender ( 7), (91,97,(99)(100)(101)(102)(103) and seasonality (3). (97,104,105).…”
Section: Bmi: Body Massmentioning
confidence: 99%
“…(102) A study among adolescents found the odds of having a severe type of depression were twice among female cisgender, compared to LGBQ2S + and food insecure adolescents. (103) Studies found seasonal variations in mental health. Winter months (October-March) accounted for around three quarters of the total psychiatric consultation referrals for Inuit clients.…”
Section: Bmi: Body Massmentioning
confidence: 99%
“…True inclusion must recognise the historical context of colonisation and its impacts on youth agency while accounting for various social dynamics, including Elder/youth and Indigenous/non-Indigenous power relations. 26 Both perpetrating and receiving IPV were associated with a higher likelihood of depression among youth in our study, which suggests a syndemic between mental health and IPV that will need to be explored in longitudinal studies to determine directionality. The correlation between highly prevalent IPV and symptoms of depression among youth in our study is consistent with the evidence of mental health hospitalisations that are almost five times higher among youths aged 15-17 in the NWT than among the general Canadian population (23.3 per 1000 people versus 4.7).…”
Section: Discussionmentioning
confidence: 71%
“…The Fostering Open eXpression Programme was a participatory action research project to promote the health and well-being of Northern and Indigenous youth, focusing on girls’ sexual and mental health and gender-diverse youth. This participatory programme used traditional beading and art-based methods to help teenage girls express their knowledge, opinions, and mental and sexual health questions 106 107…”
Section: Resultsmentioning
confidence: 99%